Genome wide analysis of chromosomal alterations in oral squamous cell carcinomas revealed over expression of MGAM and ADAM9 - Vincent-Chong, V.K.; Anwar, A.; Karen-Ng, L.P.; Cheong, S.C.; Yang, Y.H.; Pradeep, P.J.; Rahman, Z.A.A.; Ismail, S.M.; Zaini, Z.M.; Prepageran, N.; Kallarakkal, T.G.; Ramanathan, A.; et al. (Public Library of Science, 2013)
Despite the advances in diagnosis and treatment of oral squamous cell carcinoma (OSCC), mortality and morbidity rates have not improved over the past decade. A major drawback in diagnosis and treatment of OSCC is the lack of knowledge relating to how genetic instability in oral cancer genomes affects oral carcinogenesis. Hence, the key aim of this study was to identify copy number alterations (CNAs) that may be cancer associated in OSCC using high-resolution array comparative genomic hybridization (aCGH). To our knowledge this is the first study to use ultra-high density aCGH microarrays to profile a large number of OSCC genomes (n = 46). The most frequently amplified CNAs were located on chromosome 11q11(52), 2p22.3(52), 1q21.3-q22(54), 6p21.32(59), 20p13(61), 7q34(52 and 72), 8p11.23-p11.22(80), 8q11.1-q24.4(54), 9q13-q34.3(54), 11q23.3-q25(57); 14q21.3-q31.1(54); 14q31.3-q32.33(57), 20p13-p12.3(54) and 20q11.21-q13.33(52). The most frequently deleted chromosome region was located on 3q26.1 (54). In order to verify the CNAs from aCGH using quantitative polymerase chain reaction (qPCR), the three top most amplified regions and their associated genes, namely ADAM5P (8p11.23-p11.22), MGAM (7q34) and SIRPB1 (20p13.1), were selected in this study. The ADAM5P locus was found to be amplified in 39 samples and deleted in one; MGAM (24 amplifications and 3 deletions); and SIRPB1 (12 amplifications, others undetermined). On the basis of putative cancer-related annotations, two genes, namely ADAM metallopeptidase domain 9 (ADAM9) and maltase-glucoamylase alpha-glucosidase (MGAM), that mapped to CNA regions were selected for further evaluation of their mRNA expression using reverse transcriptase qPCR. The over-expression of MGAM was confirmed with a 6.6 fold increase in expression at the mRNA level whereas the fold change in ADAM9 demonstrated a 1.6 fold increase. This study has identified significant regions in the OSCC genome that were amplified and resulted in consequent over-expression of the MGAM and ADAM9 genes that may be utilized as biological markers for OSCC.